Regulation of embryonic neurogenesis by germinal zone vasculature - Tata, Mathew (Proc Natl Acad Sci U S A, 2016)
In the adult rodent brain, new neurons are born in two germinal regions that are associated with blood vessels, and blood vessels and vessel-derived factors are thought to regulate the activity of adult neural stem cells. Recently, it has been proposed that a vascular niche also regulates prenatal neurogenesis. Here we identify the mouse embryo hindbrain as a powerful model to study embryonic neurogenesis and define the relationship between neural progenitor cell (NPC) behavior and vessel growth. Using this model, we show that a subventricular vascular plexus (SVP) extends through a hindbrain germinal zone populated by NPCs whose peak mitotic activity follows a surge in SVP growth. Hindbrains genetically defective in SVP formation owing to constitutive NRP1 loss showed a premature decline in both NPC activity and hindbrain growth downstream of precocious cell cycle exit, premature neuronal differentiation, and abnormal mitosis patterns. Defective regulation of NPC activity was not observed in mice lacking NRP1 expression by NPCs, but instead in mice lacking NRP1 selectively in endothelial cells, yet was independent of vascular roles in hindbrain oxygenation. Therefore, germinal zone vascularization sustains NPC proliferation in the prenatal brain.